2016
DOI: 10.1002/pola.28065
|View full text |Cite
|
Sign up to set email alerts
|

Tough photopolymers based on vinyl esters for biomedical applications

Abstract: Photocurable vinyl esters have recently been introduced as suitable alternatives to (meth)acrylates in biomedical applications. While (meth)acrylates exhibit good mechanical properties, their cytotoxicity and degradation products principally disqualify them from medical use. Vinyl esters exhibit much lower cytotoxicity and give biocompatible degradation products, but their disadvantage are relatively low mechanical properties, particularly brittleness. This study focuses on the identification of suitable funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 53 publications
0
51
0
Order By: Relevance
“…Especially, methacrylates can also be found as prominent examples for currently applied materials used in treatment of bone injuries (as bone cement) and in dental restoratives . Nevertheless, the applicability in this field is still limited due to the cytotoxicity of (meth)acrylates and their unfavorable degradation products (polyacids) …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially, methacrylates can also be found as prominent examples for currently applied materials used in treatment of bone injuries (as bone cement) and in dental restoratives . Nevertheless, the applicability in this field is still limited due to the cytotoxicity of (meth)acrylates and their unfavorable degradation products (polyacids) …”
Section: Introductionmentioning
confidence: 99%
“…Vinyl esters (VEs) emerged as promising alternatives, showing favorable reactivity along with low cytotoxicity . However, homopolymers of, for example, divinyl adipate (DVA, the only multifunctional commercially available VE) are very brittle and frequently break during crosslinking owing the high shrinkage stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, various naturally occurring and thus renewable compounds have attracted much attention as the starting materials for developing multifunctional monomers. This is because the use of renewable compounds means a reduction in the consumption of fossil‐based resources, and provides more green and sustainable approaches to polymer materials . The focus of our research interest has been on the utilization of myo ‐inositol as a starting material for designing monomers to prepare linear and networked polymers .…”
Section: Introductionmentioning
confidence: 99%
“…This suggests a higher biocompatibility of alkyne based building blocks. Moreover, it was shown that thiols based on mercapto propionic acid derivatives provide low monomer cytotoxicity …”
Section: Introductionmentioning
confidence: 99%